Demographic predictors of nonHDL-C increase during COVID-19 pandemic stay-at-home period - Arun Manmadhan; Samuel J. Kozloff; Sean P. Heffron (Elsevier, 2021)
The onset of the coronavirus 2019 (COVID-19) pandemic prompted unique public health measures including stay-at-home (SAH) orders that provoked altered dietary and exercise patterns and may have affected medication access and use. Although these impacts have the potential to influence lipid levels, little is known of the consequences of COVID-19 SAH on objective atherosclerotic cardiovascular disease (ASCVD) risk factors. We performed a patient-level analysis of the primary measure of atherogenic lipid-associated risk, nonHDL-C during the 2020 SAH period and the same time period in 2019, in patients within a large health system in New York City. We found that women and racial and ethnic minority group members were more likely to exhibit substantial worsening of atherogenic lipid profile (≥38 mg/dL increase in nonHDL-C) during this period. Our results suggest that the pandemic and subsequent public health measures may have produced unintended negative consequences on already at-risk groups.